Spectroscopic, radiochemical, and theoretical studies of the Ga3+‐N‐2‐hydroxyethyl piperazine‐N′‐2‐ethanesulfonic acid (HEPES buffer) system: evidence for the formation of Ga3+‐ HEPES complexes in 68 Ga labeling reactions. (14th February 2013) - Martins, André F.; Prata, M. I. M.; Rodrigues, S. P. J.; Geraldes, Carlos F. G. C.; Riss, P. J.; Amor‐Coarasa, A.; Burchardt, C.; Kroll, C.; Roesch, F.
Abstract : Recent reports have claimed a superior performance of HEPES buffer in comparison to alternative buffer systems for 67/68  Ga labeling in aqueous media. In this paper we report spectroscopic ( 1 H and 71  Ga NMR), radiochemical, mass spectrometry and theoretical modeling studies on the Ga 3+ /HEPES system (HEPES =  N ‐2‐hydroxyethylpiperazine‐ N ′‐2‐ethanesulfonic acid) performed with the aim of elucidating a potential contribution of HEPES in the 68/67  Ga radiolabeling process. Our results demonstrate that HEPES acts as a weakly but competitive chelator of Ga 3+ and that this interaction depends on the relative Ga 3+ : HEPES concentration. A by‐product formed in the labeling mixture has been identified as a [ 68  Ga]Ga(HEPES) complex via chromatographic comparison with the nonradioactive analog. The formation of this complex was verified to compete with [ 68  Ga]Ga(NOTA) complexation at low NOTA concentration. Putative chelation of Ga 3+ by the hydroxyl and adjacent ring nitrogen of HEPES is proposed on the basis of 1 H NMR shifts induced by Ga 3+ and theoretical modeling studies. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We show by spectroscopic, radiochemical, chromatographic, mass spectrometry and theoretical modelling studies that the HEPES buffer acts as a weakly but competitive chelator of Ga 3+ . This observation explains its superior performance relative to alternative buffer systems for 67/68 Ga radiolabelling in aqueous media.